Il videofonino nella rete. La costruzione del panico morale nella rappresentazione giornalistica di un nuovo medium - Davide Borrelli (Quaderni di Sociologia, 2007)
Mobile videophone is one of the most innovative but socially controversial Information and Communication Technologies (ICT’s). The aim of this essay is to analyse the general feeling of «moral panic» (referring to Stanley Cohen’s theory) that is affecting today both the new media, such as mobile videophone, and the new communication practices, such as social networking on the Web 2.0 sites (see YouTube, for example). We focused on some recent episodes of cyber- or video-bullism as they have been represented by the Italian mainstream media (press, tv broadcasting). Apparently, the unanimous moral condemnation of mobile videophone especially involves its peculiar bias to point out immediately obscene and anomic contents. In our opinion, the relationships between mobile videophone and social deviance can be explained more likely by the very features of this kind of device. What is at the stake with mobile videophone is the power to produce and provide the user-generated contents out of the sphere of the mainstream media and according to a logic of «networked information economy» (to say with Iochai Benkler). This practice is deeply reshaping, acting from bottom up, the process of public scene’s construction. We noticed that, with regard to mobile videophone, most newspapers report, in emphatic terms and in a scandalous way, almost not-penally significant events, or small turbulences of everyday life that concern common morality, rather than the criminal law. Moving from this argument, we tried to look into the moral panic about mobile videophone, explaining it as an effect of a intrinsically ob-scene medium. Indeed, it promotes, gives voice and makes visible subjectivities, forms of life and provinces of meaning traditionally obscured and removed from the public sphere.